2020
DOI: 10.1053/j.gastro.2020.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D1, Reduced in Human Pancreatic Tumors, Increases Secretion of Small Extracellular Vesicles From Cancer Cells That Promote Metastasis to Lung in Mice

Abstract: BASIC AND TRANSLATIONAL PANCREAS pancreatic cancer cells showed increased loading of integrin a6b4 into sEVs-a process that required CD82. CONCLUSIONS: Human pancreatic ductal adenocarcinoma has reduced levels of PRKD1 compared with nontumor pancreatic tissues. Loss of PRKD1 results in reduced phosphorylation of cortactin in pancreatic cancer cell lines, resulting in increased in F-actin at the plasma membrane and increased release of sEVs, with altered content. These sEVs promote metastasis of xenograft and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 76 publications
3
55
0
Order By: Relevance
“…Unphosphorylated CFL1 translocates to the mitochondrion after induction of apoptosis [122][123][124][125] and acts as a carrier for BAX [126]. [130,131] TCF7L2 (active) GSE15471, GSE16515, GSE32676 (see Figure 4b) AURKA (active) GSE15471, GSE16515, GSE32676 (see Figure 4a) SSH1L (active) [ First, we concentrated on processes leading to overexpression and activation of CFL1. Following the progression towards cancer, our model shows an imbalance between the two opponents ras homolog family member A (RHOA) and ras-related botulinum toxin substrate 1 (RAC1) in favor of RAC1 (Figure 3b).…”
Section: Ssh1lmentioning
confidence: 99%
“…Unphosphorylated CFL1 translocates to the mitochondrion after induction of apoptosis [122][123][124][125] and acts as a carrier for BAX [126]. [130,131] TCF7L2 (active) GSE15471, GSE16515, GSE32676 (see Figure 4b) AURKA (active) GSE15471, GSE16515, GSE32676 (see Figure 4a) SSH1L (active) [ First, we concentrated on processes leading to overexpression and activation of CFL1. Following the progression towards cancer, our model shows an imbalance between the two opponents ras homolog family member A (RHOA) and ras-related botulinum toxin substrate 1 (RAC1) in favor of RAC1 (Figure 3b).…”
Section: Ssh1lmentioning
confidence: 99%
“…Additional evidence has demonstrated that PaCaExos that are positive for integrin αvβ5 usually reach the liver, whereas integrin α6β4- and α6β1-containing exosomes are transported to the lungs [ 116 ]. A recent study has demonstrated that protein kinase D1 (PRKD-1) expression is significantly downregulated in PaCa tissues when compared to non-tumor tissues [ 131 ]. Particularly, PRKD-1 knockout can induce PaCa cells (Panc-1) to produce more exosomes.…”
Section: Exosomes and Paca Metastasismentioning
confidence: 99%
“…Moreover, PaCa xenograft mouse experiments have confirmed that PRKD-1 knockout can increase the content of exosomes in the serum, thus promoting PaCa invasion. Mechanistic analysis has showed that alteration on PRKD-1 may stimulate PaCa cells to produce more integrin α6β4 positive exosomes to promote PaCa lung metastasis [ 131 ]. Furthermore, Li and colleagues have figured out that the formation of a pre-metastatic niche also requires the generation of new blood vessels [ 128 ].…”
Section: Exosomes and Paca Metastasismentioning
confidence: 99%
“…MVBs are involved in promoting virtually all aspects of cancer progression, including tumor expansion, immune responses, and drug resistance [2,28,30,71,143]. Studies have shown that MVBs, as important mediators of many aspects of cellular homeostasis, undergo significant changes in adapting to various stress conditions that enable cancer cells to maintain its homeostasis [3,24,40].…”
Section: Mvbs In Tumor Progressionmentioning
confidence: 99%